CD4(+) T Cells Prevent Spontaneous Experimental Autoimmune Encephalomyelitis in Anti–Myelin Basic Protein T Cell Receptor Transgenic Mice - Van de Keere, Fabienne (The Rockefeller University Press, 1998)
Autoimmune diseases result from a failure of tolerance. Although many self-reactive T cells are present in animals and humans, their activation appears to be prevented normally by regulatory T cells. In this study, we show that regulatory CD4(+) T cells do protect mice against the spontaneous occurrence of experimental autoimmune encephalomyelitis (EAE), a mouse model for multiple sclerosis. Anti–myelin basic protein (MBP) TCR transgenic mice (T/R(+)) do not spontaneously develop EAE although many self-reactive T cells are present in their thymi and peripheral lymphoid organs. However, the disease develops in all crosses of T/R(+) mice with recombination-activating gene (RAG)-1 knockout mice in which transgenic TCR-expressing cells are the only lymphocytes present (T/R(−) mice). In this study, crosses of T/R(+) mice with mice deficient for B cells, CD8(+) T cells, NK1.1 CD4(+) T (NKT) cells, γ/δ T cells, or α/β T cells indicated that α/β CD4(+) T cells were the only cell population capable of controlling the self-reactive T cells. To confirm the protective role of CD4(+) T cells, we performed adoptive transfer experiments. CD4(+) T cells purified from thymi or lymph nodes of normal mice prevented the occurrence of spontaneous EAE in T/R(−) mice. To achieve full protection, the cells had to be transferred before the recipient mice manifested any symptoms of the disease. Transfer of CD4(+) T cells after the appearance of symptoms of EAE had no protective effect. These results indicate that at least some CD4(+) T cells have a regulatory function that prevent the activation of self-reactive T cells.